2011
DOI: 10.4103/0970-9185.86586
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic stress response during laparoscopic cholecystectomy: Effect of two different doses of intravenous clonidine premedication

Abstract: Background:Clonidine has emerged as an attractive premedication desirable in laparoscopic surgery wherein significant hemodynamic stress response is seen. The minimum safe and effective dose of intravenous clonidine to attenuate the hemodynamic stress response during laparoscopic surgery has however not yet been determined.Materials and Methods:This prospective, randomized, double-blind controlled study was conducted on 90 adults of ASA physical status I and II, scheduled for laparoscopic cholecystectomy under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 13 publications
(16 reference statements)
2
32
0
Order By: Relevance
“…Tripathi et al in has studied that Clonidine, 2 μg/ kg intravenously, 30 min before induction is safe and effective in preventing the hemodynamic stress response during laparoscopic cholecystectomy [9] . Sameena kousar et al compared effect of Fentanyl and Clonidine for attenuation of the haemodynamic response to laryngocopy and endotracheal intubation and found that Clonidine showed better attenuation of the sympathetic response [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Tripathi et al in has studied that Clonidine, 2 μg/ kg intravenously, 30 min before induction is safe and effective in preventing the hemodynamic stress response during laparoscopic cholecystectomy [9] . Sameena kousar et al compared effect of Fentanyl and Clonidine for attenuation of the haemodynamic response to laryngocopy and endotracheal intubation and found that Clonidine showed better attenuation of the sympathetic response [10] .…”
Section: Discussionmentioning
confidence: 99%
“…[21] Dose selection is in consensus with previous studies by Tripathi et al . [17] We chose to administer IM clonidine 60-90 min prior to induction and IV clonidine 15 min prior to induction. In view of the fact that, clonidine has a half-life of 8-12 hrs with peak effect achieved in 1-1.5 hrs after IM administration and 20 minutes after IV administration.…”
Section: Discussionmentioning
confidence: 99%
“…[7141516] There are few studies demonstrating the effectiveness of intravenous (IV)[1718] or intramuscular (IM)[1920] clonidine individually in attenuation of hemodynamic response during laparoscopy. However, there is limited literature, comparing the intravenous and intramuscular routes of clonidine premedicant in laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Clonidine (category B-2). Clonidine is a centrally acting a agonist used to treat central pain syndromes; however, evidence suggests a useful role as an opioid-sparing medication with anesthesia and analgesia (Blaudszun, Lysakowski, Elia, & Tramer, 2012;Tripathi, Shah, Dubey, Doshi, & Raval, 2011). Studies document increased sedation when clonidine is added to opioid-based regimens (Huang et al, 2007;McCartney, Duggan, & Apatu, 2007;Vukovic, Ramakrishnan, & Milan, 2012) but no appreciable effects of clonidine in causing respiratory depression.…”
Section: Rationalementioning
confidence: 99%